Bioinformatics Analysis of Hub Genes and Potential Therapeutic Agents Associated with Gastric Cancer - Zhang S (Dove Medical Press, 2021)
Shiyu Zhang, Xuelian Xiang, Li Liu, Huiying Yang, Dongliang Cen, Guodu Tang Department of Gastroenterology, The First Affiliated Hospital of Guangxi Medical University, Nanning City, Guangxi Province, People’s Republic of ChinaCorrespondence: Guodu TangDepartment of Gastroenterology, The First Affiliated Hospital of Guangxi Medical University, 22 Shuangyong Road, Nanning City, Guangxi Province, People’s Republic of ChinaTel +86 13739139408Email tangguodu@stu.gxmu.edu.cnPurpose: The current treatment methods available for advanced gastric cancer are not very promising. Hence, it is important to explore novel biomarkers and potential therapeutic agents to treat gastric cancer (GC). This study aimed to identify hub genes associated with GC prognosis and explore potential drugs for its treatment.Materials and Methods: Three gene expression data of GC and normal tissues were downloaded from the Gene Expression Omnibus (GEO) and processed to identify the differentially expressed genes (DEGs). We conducted a comprehensive analysis of DEGs, including functional enrichment analysis, construction of protein–protein interaction (PPI) network, identification of hub genes, survival analysis and expression verification of hub genes. Finally, we constructed the network of miRNA–mRNA, and predicted the drugs that might be effective for GC treatment.Results: A total of 340 DEGs, including 94 up-regulated and 246 down-regulated genes, were identified. Among the up-regulated DEGs, the enrichment terms were primarily related to tumorigenesis and tumor progression, extracellular matrix organization, and collagen catabolic process. Additionally, 10 hub genes (FN1, COL3A1, COL1A2, BGN, THBS2, COL5A2, THBS1, COL5A1, SPARC, and COL4A1) were identified, out of which 7 genes were significantly associated with poor overall survival (OS) in GC. The expression levels of these 7 hub genes were verified using real-time PCR, immunohistochemistry, and the GEPIA2 (Gene Expression Profiling Interactive Analysis) server. A regulatory network of miRNA–mRNA was also constructed, and the top 4 interactive miRNAs (hsa-miR-29b-3p, hsa-miR-140-3p, hsa-miR-29a-3p, and hsa-miR-29c-3p) that targeted the most hub genes were identified. Finally, fourteen small molecules were predicted to be effective in treating GC.Conclusion: The identification of the hub genes, miRNA–mRNA network, and potential candidate drugs associated with GC provides new insights into the molecular mechanisms and treatment of GC.Keywords: gastric cancer, prognosis, bioinformatics, biomarkers